West African agriculture for jobs, nutrition, growth, and climate resilience - Wiebe, Keith D.; Stads, Gert-Jan; Beintema, Nienke M.; Brooks, Karen; Cenacchi, Nicola; Dunston, Shahnila; Mason-D'Croz, Daniel; Sulser, Timothy B.; Thomas, Timothy S. (International Food Policy Research Institute, 2017)
The regional agrifood system described above is complex and raises significant managerial challenges for decision makers. It is not, however, new or a radical departure from the system that is already in place and evolving. In addition to the specific messages summarized above, this report emphasizes the importance of and benefits from applying analytical tools in decision making for agricultural transformation. A sample of such tools is presented in this report. The applications of the tools and findings herein reported are sound, but also limited by context and availability of data.